The Influence of Entrepreneurship Education and Its Implementation - Herdinata, Christian (Universitas Katolik Darma Cendika, 2024)
Research related to entrepreneurial education (EU) and its implementation is very important to develop entrepreneurial abilities. Therefore, this research was conducted to determine the influence of EU and its implementation in relation to entrepreneurial capacity (EC), entrepreneurial passion (EP) and entrepreneurial intentions (EI). EC is a person's ability to find, recognize and absorb opportunities before undertaking. Furthermore, PE is the motivating force to influence the recognition by seeing opportunities, the vision, the mission, the decisions and the perseverance to get involved in the business to be built. Furthermore, PE is a person's thinking to form new business concepts and have a career in it. world of entrepreneurship. This research uses a literature study method by reviewing the results of previous research following the steps: (1) identify the research topic to be studied; (2) collect library sources that are relevant to the research topic; (3) read and analyze these library sources comprehensively; (4) identify findings and information relevant to the research topic; (5) organize and compile the findings in the form of a research report. The results of this research show that the EU in its implementation influences the EC, the EP and the EI. Furthermore, this research shows that the EU, EC and EP influence EI. Therefore, educational institutions that want to develop entrepreneurial skills can implement a curriculum based on project-based learning and problem-based learning so that students can directly experience concrete entrepreneurial learning in terms of knowledge, skills and experience. so that they can increase their entrepreneurial intentions and can even develop the business that they have been running since they were students.